A Study on the Prospects and Constraints of Rural Tourism Promotion Through Social Media in Southern Rajasthan - Nikita Maheshwari; Dr. Namrata Khemraj Yadav (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper explores the prospects and challenges of using social media to promote rural tourism in Southern Rajasthan, an area with a strong cultural heritage but economic limitations. Low levels of digital literacy, limited internet access, and cultural sensitivities constitute barriers to engaging local communities and attracting tourists; however, social media holds much promise. This paper applies ANOVA to the perception that demographic differences affect social media's role in tourism promotion by collecting primary data using questionnaires. The outcome indicated social media as one relatively inexpensive marketing tool for hosting community participation and greater worldwide exposure for region-specific attractions. The study therefore identifies major limitations and influential factors in using social media to balance cultural sensitivities with broader economic opportunities for sustainable tourism growth.